Awareness of the cannabis consumption in Spain: study of the approach through the scientific field and press - Alonso Ayuso, Ana Teresa (Revista Española de Comunicación en Salud, 2020)
Introduction: In Spain, the recreational use of cannabis is illegal. This illegality is once again part of a social debate in which certain political groups support a justified legalization based on economic benefits against some medical opinions that do not recommend the consumption decriminalization. Objective: This review aims to identify the approach given to consumption in Spain, both in the scientific field and in a more general one as the written press. The coherence or disagreement between the detected approaches can contribute to determinate if legalization will be a reality soon. Method: An analysis of scientific and non-scientific publications is carried out using three forms of research: a specialized search tool (Google Scholar), two national newspapers in their digital version (ABC and El País) and an online scientific citation indexing service (Web of Science). Results: The journalistic and the scientific field coincide in a negative approach regarding the cannabis consumption; in addition, its content turns out to be very focused on society. Conclusions: The high consumption of cannabis among the Spanish population despite the negative approach indicates a failure in the communication related with this problematic.
Keywords: cannabis; consumption; legalization; sociology; press; Spain